Demonstration of Gall Bladder Surgery in Patients Coming to Tertiary Care Hospital: Population Awareness - Muhammad Kamran Khan, Faryal Saeed, Marrium Khurshid, Ibrar Ahmad, Saad Ali Shah, Ajmal Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To demonstrate gall bladder surgery in patients for population awareness. Study Design: Retrospective study Place and Duration of Study: Department of Surgery, Abbottabad International Medical Institute, Abbottabad from 1st October 2020 to 30th September 2021. Methodology: Two hundred patients with clinical symptoms of gall bladder stones were admitted. Each patient demographic, clinical, biochemical analysis and radiological imaging was performed for confirmation of gall stones and their size. The age was divided in to two sub groups for better demonstration. Pre and post operative complications were documented and compared within ages. Surgical Laparoscopic procedure was opted as a first choice for cholecystectomy. Results: The mean age of the patients as 32.3±4.4 with 70% being females. Majority of the patients were complained bloating and right upper quadrant pain. Around 91.8% of the patients were operated through laparoscopic. The mean time for operation was 50 minutes in both age groups. The post operative complications suggested as lower respiratory tract infection as more common in post operative cases of older adults where as younger adults had higher frequency of superficial thrombophlebitis. No case of mortality was documented. Conclusion: Gall bladder surgery is a safe procedure which can timely save lives.